2015
DOI: 10.1007/978-3-319-16462-5_7
|View full text |Cite
|
Sign up to set email alerts
|

LabelFlow: Exploiting Workflow Provenance to Surface Scientific Data Provenance

Abstract: Abstract. Provenance traces captured by scientific workflows can be useful for designing, debugging and maintenance. However, our experience suggests that they are of limited use for reporting results, in part because traces do not comprise domain-specific annotations needed for explaining results, and the black-box nature of some workflow activities. We show that by basic mark-up of the data processing within activities and using a set of domain specific label generation functions, standard workflow provenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the architecture discussion, three papers were presented: noWorkflow [80] is a tool that transparently captures provenance of scripts and enables reproducibility, LabelFlow [46] uses domain-specific labels with workflow provenance as a platform for data artifacts labelling; and [84] proposes software provenance to be included as part of software packages.…”
Section: Provenancementioning
confidence: 99%
“…In the architecture discussion, three papers were presented: noWorkflow [80] is a tool that transparently captures provenance of scripts and enables reproducibility, LabelFlow [46] uses domain-specific labels with workflow provenance as a platform for data artifacts labelling; and [84] proposes software provenance to be included as part of software packages.…”
Section: Provenancementioning
confidence: 99%
“…Provenance Explorer was designed to provide a customizable visualization of the provenance trail associated with scientific discovery processes by utilizing both explicit and implicit RDF relationships [130]. LabelFlow is a tool to manipulate the workflow provenance of scientific data in RDF [131]. It enables semi-automated provenance annotation and can handle PROV-O-and WFPROV-compliant provenance traces.…”
Section: Software Tools For Manipulating Rdf Provenancementioning
confidence: 99%
“…Regarding the third problem, it has long been recognized that semantic labeling is a central automation task for the semantic web, as users tend to avoid the extra manual work involved. For this purpose, it has been suggested that the provenance information contained in workflows can be used to add semantic labels to the nodes in such a workflow (Alper et al 2014). For the geospatial domain, it was demonstrated that the information contained in GIS workflows can be used to enrich geodata as well as GIS tools with important semantic types by traversing such a workflow, and share this information as linked data (Scheider and Ballatore 2018).…”
Section: Service Metadata Computational Core Concepts Linked Data Amentioning
confidence: 99%